Hepatic portal venous gas does not show the severity of intestinal ischaemia - Yildirim, Kadir; llhan Karabicak; Mahmut Fikret Gursel; Ozturk, Bahadir; Zafer Malazgirt (Journal of the Pakistan Medical Association, 2022)
Hepatic portomesenteric venous gas is a rare condition. Although a CT scan can show hepatic portal vein gas, the intestine’s condition can still be misdiagnosed at the very early stage. Accordingly, the decision to operate has to be made based on or after a physicial examnination and laboratory results. In this report, we present a case of portomesenteric venous gas in which the gas was no longer discernible on the control CT scan, even though the patient developed peritonitis. Keywords: portomesenteric venous gas, intestinal ischemia, peritonitis.